Cold Atmospheric Plasma Improves the Therapeutic Success of Photodynamic Therapy on UV-B-Induced Squamous Cell Carcinoma in Hairless Mice - Stephanie Arndt; Petra Unger; Irina Ivanova; Wolfgang Bäumler; Konstantin Drexler; Mark Berneburg; Sigrid Karrer (Pharmaceuticals)
Background/Objectives: Actinic keratosis (AK) occurs on sun-damaged skin and is considered a precursor to squamous cell carcinoma (SCC). Photodynamic therapy (PDT), using 5-aminolevulinic acid (ALA) and red light, is a common treatment for AK. However, its clinical efficacy for invasive tumors such as SCC is limited by the poor penetration and distribution of the photosensitizer. Cold atmospheric plasma (CAP), a partially ionized gas, increases skin permeability and exhibits anti-cancer properties through the generation of reactive oxygen species (ROS). In a previous study, CAP showed promising synergistic effects when combined with ALA-PDT for the treatment of SCC cells in vitro. The present study investigated the effects of combining CAP with ALA-PDT on cutaneous AK and SCC induced by ultraviolet B (UV-B) irradiation in SKH1 hairless mice. Methods: We compared various application sequences (CAP-ALA–red light, ALA–red light–CAP, and ALA-CAP–red light) against conventional ALA-PDT using visual, histological, and molecular assessments of the affected skin. Results: The results demonstrated that combined treatments strongly inhibited the growth of UV-B-induced skin lesions. TUNEL staining revealed increased apoptosis following both single and combined therapies, while Ki-67 staining indicated reduced keratinocyte proliferation and diminished DNA damage in treated areas. mRNA expression analysis showed the upregulation of apoptosis-related genes (p16INK4a, p21CIP1) alongside enhanced anti-tumor immune responses (IL-6, IL-8) in the affected tissue samples. Notably, the combined treatment enhances the therapeutic effect, whereas the sequence of application does not seem to be relevant for therapeutic efficacy in vivo. Conclusions: Overall, these results suggest that CAP may enhance the anti-tumor effect of conventional ALA-PDT, supporting previous findings on SCC cells.